(untitled) (Світ фінансів, 2017)
Кириленко О. П. Актуальні проблеми реформування бюджетної системи України. Розглянуто окремі аспекти функціонування бюджетної системи України, практики формування та використання коштів державного та місцевих бюджетів, організації міжбюджетних відносин. Виявлено низку негативних тенденцій і окреслено шляхи вирішення існуючих проблем з врахуванням визначених пріоритетів суспільного розвитку. Kyrylenko O. The actual issues of the budget-funded system reformation of Ukraine. The certain aspects of budget-funded system functioning of Ukraine, practical forming and using of state and local budgets funds, interbudgetary relations organizing are considered. The chain of negative tendencies is exposed, and the ways of existing issues determination are outlined taking into consideration the identified priorities of social development.